Entre rumores de guerra e musicalidades : histórias em meio à educação inclusiva - Kuster, Patrick Stefenoni (2013)
The Municipal Secretariat of Education and Sports Domingos Martins (ES) has been articulating policies of inclusive education / special education from the perspective of inclusion (BRAZIL, 2008). Accordingly, in order to meet the disabled into the regular school system, she organized the Reference Center on Inclusive Education. But who is taking the stage are not disabled, but the "aggressive students", "hyperactive", "violent". Of daily exercise psi comprising the Reference Center, we look into what these students have been saying. This allows an opening to direct testimony, putting in analyzing the implications of the reference equipment in its multifaceted relationship with municipal schools of education. In this trajectory, inclusive education will bringing out ways to occupy the town of Domingos Martins, a certain distribution of seats. These students brought in the thickness of their bodies, shades of unknown worlds, of the great cities irreducible city tourism, poor communities, men s field, the streets were not the of Pedra Azul, inconceivable dimensions to the crackle of human rationality negligible , a strangeness mute, a whisper of darkness.